2021
DOI: 10.1016/j.isci.2021.102920
|View full text |Cite
|
Sign up to set email alerts
|

Common and unique strategies of myoglobin evolution for deep-sea adaptation of diving mammals

Abstract: Summary Myoglobin (Mb) is highly concentrated in the myocytes of diving mammals such as whales and seals, in comparison with land animals, and its molecular evolution has played a crucial role in their deep-sea adaptation. We previously resurrected ancestral whale Mbs and demonstrated the evolutional strategies for higher solubility under macromolecular crowding conditions. Pinnipeds, such as seals and sea lions, are also expert diving mammals with Mb-rich muscles. In the present study, we resurrect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…The O 2 -storage protein myoglobin (Mb) is known to be expressed in myocytes of diving mammals such as seals and whales at much higher concentrations than those of land animals, which contributes to their diving ability in oceans. Mirceta et al (2013) indicated that diving animal Mbs have developed increased positive charges during evolution from their ancient land animal predecessors to adapt to the deep-sea environment, based on the prediction of amino acid sequences of their ancestral Mbs, and concluded that the higher Mb concentration in their muscle tissues is enabled by the electrostatic repulsion between Mb molecules. Dasmeh et al (2013) suggested that thermodynamic stabilities of whale Mbs had increased during the molecular evolution for deep sea adaptation, based on their theoretical prediction of folding stability from the 3D models of the ancestral Mbs. , We have synthesized ancient whale and seal Mbs and experimentally confirmed that both the positive surface charges and folding stability had been increased during evolution. , Furthermore, solubility tests were performed in the presence of PEG and indicated that the diving mammal Mbs had evolved increased tolerance against precipitant or macromolecular crowding, rather than increased solubility in a dilute buffer solution. However, chemical mechanisms of the precipitant tolerance remain unclear.…”
mentioning
confidence: 60%
See 4 more Smart Citations
“…The O 2 -storage protein myoglobin (Mb) is known to be expressed in myocytes of diving mammals such as seals and whales at much higher concentrations than those of land animals, which contributes to their diving ability in oceans. Mirceta et al (2013) indicated that diving animal Mbs have developed increased positive charges during evolution from their ancient land animal predecessors to adapt to the deep-sea environment, based on the prediction of amino acid sequences of their ancestral Mbs, and concluded that the higher Mb concentration in their muscle tissues is enabled by the electrostatic repulsion between Mb molecules. Dasmeh et al (2013) suggested that thermodynamic stabilities of whale Mbs had increased during the molecular evolution for deep sea adaptation, based on their theoretical prediction of folding stability from the 3D models of the ancestral Mbs. , We have synthesized ancient whale and seal Mbs and experimentally confirmed that both the positive surface charges and folding stability had been increased during evolution. , Furthermore, solubility tests were performed in the presence of PEG and indicated that the diving mammal Mbs had evolved increased tolerance against precipitant or macromolecular crowding, rather than increased solubility in a dilute buffer solution. However, chemical mechanisms of the precipitant tolerance remain unclear.…”
mentioning
confidence: 60%
“…16,17 We have synthesized ancient whale and seal Mbs and experimentally confirmed that both the positive surface charges and folding stability had been increased during evolution. 18,19 Furthermore, solubility tests were performed in the presence of PEG and indicated that the diving mammal Mbs had evolved increased tolerance against precipitant or macromolecular crowding, rather than increased solubility in a dilute buffer solution. However, chemical mechanisms of the precipitant tolerance remain unclear.…”
mentioning
confidence: 99%
See 3 more Smart Citations